2012
DOI: 10.1073/pnas.1114033109
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral heterogeneity of receptor tyrosine kinases EGFR and PDGFRA amplification in glioblastoma defines subpopulations with distinct growth factor response

Abstract: Glioblastoma (GBM) is distinguished by a high degree of intratumoral heterogeneity, which extends to the pattern of expression and amplification of receptor tyrosine kinases (RTKs). Although most GBMs harbor RTK amplifications, clinical trials of small-molecule inhibitors targeting individual RTKs have been disappointing to date. Activation of multiple RTKs within individual GBMs provides a theoretical mechanism of resistance; however, the spectrum of functional RTK dependence among tumor cell subpopulations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
396
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 471 publications
(413 citation statements)
references
References 38 publications
12
396
0
3
Order By: Relevance
“…S9). In agreement with previous reports on the low frequencies of mosaic coamplification of EGFR and PDGFRA in gliomas (26,27), coamplification of EGFR and PDGFRA was observed in 10 of 123 EM +++ gliomas and 2 of 36 PM ++ (Chr7 Amp) gliomas of the TCGA mRNA-seq data set, but not in the other EM/PM subgroups (SI Appendix, Fig. S2).…”
Section: Resultssupporting
confidence: 80%
“…S9). In agreement with previous reports on the low frequencies of mosaic coamplification of EGFR and PDGFRA in gliomas (26,27), coamplification of EGFR and PDGFRA was observed in 10 of 123 EM +++ gliomas and 2 of 36 PM ++ (Chr7 Amp) gliomas of the TCGA mRNA-seq data set, but not in the other EM/PM subgroups (SI Appendix, Fig. S2).…”
Section: Resultssupporting
confidence: 80%
“…We did not assess regional heterogeneity of EGFR gene amplification. However, previous studies reported that EGFR amplification may be restricted to subpopulations of tumor cells, as determined in cases of glioblastomas with amplification of EGFR and PDGFRA (52,53). With respect to EGFRvIII expression, our data demonstrate that EGFRvIII immunopositivity shows marked regional heterogeneity and is often restricted to subpopulations of tumor cells in glioblastomas, thus confirming previous findings in the GGN patient cohort (17) and in several independent studies (39,42,43,51,54).…”
Section: Discussionsupporting
confidence: 80%
“…These analyses show that ERBB2 þ tumors are composed of subpopulations of MET À /ERBB2 þ , MET þ /ERBB2 À , and MET þ /ERBB2 þ cells. These diverse expression patterns support the results of several studies in other cancer types that have shown intratumoral heterogeneity (3,25) and which have significant implications for the development of optimal treatment strategies.…”
Section: Met and Erbb2 Are Coexpressed In Subpopulations Of Cells In supporting
confidence: 72%